Evaluation of Diesel Fuel Product Quality During Storage Processes Using Qualitative Statistical Methods - Muhammad Aly Akbar; Faysa Wintang Navira; Rio Adrian Nova; Juakem Kemong; Oksil Venriza (Journal of Applied Sciences, Management and Engineering Technology, 2025)
Fuel quality greatly affects engine performance and emissions, making it essential to routinely test its physical characteristics. This study aims to analyze fuel quality by measuring ash content, density, specific gravity (SG), and API gravity of various types of fuels used in Indonesia. The study also evaluates the stability and consistency of fuel quality through repeated tests and identifies the characteristics of each fuel that affect combustion and engine performance, providing recommendations for the most optimal fuel based on the test results. The research was conducted at the PEM Akamigas Quality Control Laboratory to test fuel samples through laboratory analysis using specified equipment and materials. The tools used include filter paper, beakers, volumetric pipettes, funnels, porcelain and optical crucibles, supported by an analytical balance, tweezers, bulb, oven, desiccator, and aluminum foil for various testing stages. The fuels tested include Pertamax Turbo 98, Pertamax 92, X mix (92 mix 98), biosolar, Fatty Acid Methyl Ester (FAME), and Dexlite mixed with FAME. The results of the study show that FAME, Biosolar, and Dexlite have ash content characteristics that affect combustion and engine performance. FAME supports consistent combustion with medium and stable ash content. Biosolar produces environmentally friendly combustion with the lowest ash content, while Dexlite has the highest ash content with high consistency but may leave residue. Pertamax Turbo and Pertamax show high stability and consistency in density, SG, and API gravity, making them reliable fuels for various usage conditions.